THE EFFECT OF LEARNING MODEL LEARNING LEARNING WITH YOUTUBE VERSUS MEDIA FLASH CARD MEDIA AND LEARNING MOTIVATION ON LEARNING OUTCOMES IN ENGLISH - Rahesa Nalendra; Iskandar Wiyokusumo; Ibut Priono Leksono (Journal of English Educational Study (JEES), 2020)
Learning models only emphasize rote thinking, reproductive and looking for the right answer. Many English teachers only emphasize the theoretical aspects, not the actual function, communication skills. This study aims to determine the effect of active learning model learning with Youtube media versus flash card media and students' learning motivation towards student learning outcomes in SMP N 1 Sidoarjo and SMP N 4 Sidoarjo. The study was conducted with a quantitative approach with a factorial design experimental model. The results showed learning outcomes between learning English using active learning models with Youtube media and learning English with flash card media.